Surgical management of metastatic lesions in the proximal femur: a systematic review - Afrim Iljazi; Mads Sten Andersen; Stig Brorson; Michael Mørk Petersen; Michala Skovlund Sørensen (EFORT Open Reviews)
Purpose: The proximal femur is a frequent site of cancer dissemination in the extremities. Patients treated surgically for skeletal metastases have poorer overall health compared to other orthopedic patients, with only one-third expected to survive two years post-surgery. Choosing a treatment that minimizes revision risk and ensures the implant outlives the patient is therefore crucial. We conducted a systematic review to assess the revision rate following internal fixation (IF) or endoprosthetic reconstruction (EPR) of the proximal femur for metastatic bone disease (MBD). Methods: This study adhered to the PRISMA guidelines. MEDLINE and Embase were searched, identifying 10,299 records. After removing duplicates, 7731 unique records were screened, 334 of which were retrieved for full-text screening. We included 34 studies in the qualitative synthesis. The MINORS instrument was used for quality assessment. Results: The quality of the included studies was low to moderate, with median scores of 6/16 for non-comparative studies and 10/24 for comparative studies. We therefore refrained from a comparative analysis. Revision rates varied between 0 and 12.4% following EPR (25 studies) and between 0 and 26.7% following IF, while implant removal rates ranged between 0 and 8.3% and 0 and 26.7%, respectively. Conclusions: Revision and implant removal rates for various methods of EPR and IF are satisfactory. However, a meta-analysis or comparison between IF and EPR is not feasible due to a lack of prospective studies, randomized trials and high-quality studies.